Stosunek św. Ireneusza z Lyonu do innowierców - Balwierz, Marian (Vox Patrum, 1986)
The full approach of St. Irenaeus to the phenomenon of the heretical movements was shaped by his Christian faith. This fact allowed him first to see the nature of every heresy as an opposite reality to the Church's evangelization.